ANALISA RASIO LAPORAN KEUANGAN SEBAGAI EVALUASI KINERJA KEUANGAN PERUSAHAAN PADA RSIA KARUNIA BUNDA TANGERANG - Ermanuri Ermanuri (JURNAL LENTERA AKUNTANSI, 2018)
ABSTRACTRSIA Karunia Bunda is a mother and child hospital in Tangerang area of Banten.This research took the object RSIA Karunia Bunda in the period 2011 and 2012. The purpose of this research is to determine the condition of RSIA Karunia Bunda financial statements in the period 2011 and period 2012. Besides that also to knowand evaluate financial performance RSIA Karunia Bunda in the period 2011 and 2012. The type of research used in this research isdescriptive. While the research method is quantitative, because there are numbers and calculations using the formula. Analytical tool used is theratio of liquidity, solvability ratio and profitability ratio. Judging from the liquidity ratio, solvability ratio and profitability ratio from2011 to 2012, the performance of RSIA Karunia Bunda shows good progress, because it can be shown from the increasing sales and net profit also increased. Besides, the obligations can be fulfilled smoothly, although it should be further enhanced the sales turnover and cost efficiency, so that the company’s stability will be maintened well.Keywords: Financial Performance, Liquidity Ratio, Solvability Ratio, and Profitability Ratio.